Effect of aromatherapy with Matricaria chamomilla in pain and anxiety management in hospital settings: A scoping review protocol - Maria Améllia Lopes Cabral; Karena Cristina da Silva Leal; José Joandson de Souza dos Santos; Fernanda de Castro Teixeira; Ana Beatriz Santos Trindade; Auanna Beatriz Sarmento de Araújo Miranda; Lara Dantas de Rubim Costa; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (PLoS ONE, 2026)
Introduction Pain and anxiety are underestimated complications in hospitalized patients, negatively impacting their well-being and physiological functioning. Integrative and Complementary Health Practices (ICHP) emerge as alternatives or complements to standard treatments, with chamomile aromatherapy highlighted for its sedative, anxiolytic, and analgesic properties. Objective This review aims to map the existing knowledge regarding the use of aromatherapy with chamomile essential oil in the management of pain and anxiety within hospital environments. Method This study is a scoping review that adheres to the Joanna Briggs Institute (JBI) guidelines and the PRISMA-ScR checklist. A comprehensive search will be conducted across ten data sources for this review: Medical Literature Analysis and Retrieval System Online (MEDLine/PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, LILACS, Scielo, Cochrane Library, Scopus, ScienceDirect, Wiley Online Library, and Virtual Health Library (VHL). The selection of studies will include full-text articles, dissertations, theses, ministerial ordinances, and guidelines, while abstracts, letters to the editor, opinion articles, off-topic studies, and duplicates will be excluded.Results will be presented through a PRISMA-ScR flowchart and tables, employing the PAGER methodology to enhance reporting quality. Conclusion Aromatherapy with chamomile essential oil shows promising results for managing pain and anxiety in hospital settings. It demonstrates mild analgesic effects and consistent anxiety reduction, especially when administered via inhalation. This review aims to systematize existing knowledge, identify gaps, and provide theoretical and practical support for its safe clinical application, thereby strengthening integrative practices and promoting more humanized care.